Physical-Chemical Characteristics and Soil Classification of Lowland Alluvial Land Using Three Soil Classification Systems - Basuki Basuki; Marga Mandala; Oria Alit Farisi; Vega Kartika Sari; Suci Ristiyana; Ratih Apri Utami (The University of Lampung, 2023)
The total area of irrigated rice fields on the slopes of Mount Argopura is 21,420.02 hectares. Soil that experiences flooding will change the characteristics of the physical, chemical, and soil classification properties. The aim of the study was to examine the soil characteristics and classification system of paddy fields on the slopes of Mount Argpura. The research was conducted in July–September 2022 in paddy fields on the slopes of Mount Raung. Soil analysis in the laboratory of the Faculty of Agriculture, University of Jember This research uses a descriptive exploratory method through field surveys. Parameter research on the chemical-physical characteristics of soil and soil classification The research shows that the average rainfall of paddy fields at the foot of Mount Argopura is 2,275 mm per year with a standard deviation of 514 mm and a coefficient of variance of 23%. The morphological horizons of the genesis results in paddy fields are generally Apg, Adg, Bwg, and Cg. The USDA's classification of soil Hydraquentic Humaquepts (pedon 1), Typic Epiaquepts (pedon 2), Aeric Epiaquepts (pedon 3), Indonesian soil classification Gleisol molik (pedon 1), Gleisol eutric (pedon 2), and Gleisol eutric (pedon 3), according to WRB/FAO Molic epireductic Gleisol (Aphihumic) (pedon 1), ochric reductive gleysol (ochric, clayic) (pedon 2), and ochric siltic reductive gleysol (pedon 3). Keywords: Mount Argopura, Rice fields, Tillage, Volcanics